Comments on unintelligibility (2015)
This text consists of a review of the main concepts on which the work for string quartet "Comments on unintelligibility" is based. The purpose of this preamble is to present the concerns that the composer had at the time of writing his work. The above, through reflection on some of the ideas presented by Lerdahl (1992) in relation, first, with the compositional systems and, second, with how the resulting works are perceived and understood by the listener through the cognitive limits that he proposes. Following this preamble, the reader can find the score of the work already mentioned.